1988
DOI: 10.1111/j.1476-5381.1988.tb11489.x
|View full text |Cite
|
Sign up to set email alerts
|

The potential anxiolytic activity of GR38032F, a 5‐HT3‐receptor antagonist

Abstract: 1 The highly selective 5-HT3-receptor antagonist, GR38032F, has been tested in five animal models predictive for anxiolytic activity. 2 In the social interaction test in the rat and in a light/dark exploration test in the mouse, GR38032F dose-dependently released suppressed behaviour without modifying locomotor activity. 3 In the cynomolgus monkey and the marmoset, GR38032F reduced anxiety-related symptoms without causing sedation. In the marmoset, the effects were clearly dose-related. 4 GR38032F did not have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(94 citation statements)
references
References 16 publications
6
87
1
Order By: Relevance
“…Moreover, locomotor activity by both genotypes decreased as a function of time in the open-field environment (F time (5,150) ¼ 13.55, po0.001), which indicates normal habituation to the environment. This finding is consistent with our previous report (Kelley et al, 2003) and supports pharmacological evidence, which indicates that 5-HT 3 receptor antagonists have no effects on locomotor behavior (Jones et al, 1988).…”
Section: Locomotor Activitysupporting
confidence: 94%
“…Moreover, locomotor activity by both genotypes decreased as a function of time in the open-field environment (F time (5,150) ¼ 13.55, po0.001), which indicates normal habituation to the environment. This finding is consistent with our previous report (Kelley et al, 2003) and supports pharmacological evidence, which indicates that 5-HT 3 receptor antagonists have no effects on locomotor behavior (Jones et al, 1988).…”
Section: Locomotor Activitysupporting
confidence: 94%
“…Evidence from radioligand binding studies (Kilpatrick et al, 1987;Peroutka & Hamik, 1988;Waeber et al, 1989) and behavioural tests (Costall et al, 1987;Jones et al, 1988) have shown that 5-HT3 receptors exist not only in the periphery but also in the central nervous system. 5-HT3 receptors appear most promising as targets for novel drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it seems that stimulation of the 5-HT system results in an anxiogenic effect, while a reduction in inappropriately elevated 5-HT neuronal activity leads to anxiolysis. Accordingly anxiolytic activity has recently been reported for 5-HT3 receptor antagonists (Jones et al, 1988;Lecrubier et al, 1990). Administration of cholecystokinin (CCK), a major neuropeptide in the central nervous system (Vanderhaeghen et al, 1975;Dockray, 1976) has been found to induce anxiety both in the experimental animal and in man and CCK receptor antagonists have been shown to display anxiolytic activity (see review by Ravard & Dourish, 1990, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…social phobia, particularly as the 5-HT3 receptor antagonist, ondansetron, which has anxiolytic-like effects in the test (Jones et al, 1988;Blackburn et al, 1993), but not in the GellerSeifter procedure (Tyers et al, 1987;Piper et al, 1988), has recently been reported to be effective in clinical trials (Bell & DeVeaugh-Geiss, 1994).…”
Section: Effectsmentioning
confidence: 99%